2007
DOI: 10.2174/092986707782023307
|View full text |Cite
|
Sign up to set email alerts
|

Fish Oils and Vascular Disease Prevention: An Update

Abstract: Considerable epidemiological data confirmed the existence of favorable associations between fish consumption and mortality from cardiovascular disease. Accumulating evidence suggests that n-3 polyunsaturated fatty acids supplementation is an effective additive treatment for the primary and secondary prevention of cardiovascular disease. Another indication for the use of n-3 PUFA is the treatment of hypertriglyceridemia as monotherapy or in combination with other lipid lowering agents (e.g. statins or fibrates)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 93 publications
(214 reference statements)
0
18
0
1
Order By: Relevance
“…The latest overview found about the effect of omega-3 fatty acids in rheumatoid arthritis was published in 1998 (Ariza-Ariza, MestanzaPeralta, & Cardiel, 1998) although there is a more recent one (2006) not published in English (Stancík, Rovenský, & Stančíková, 2006). Several recent reviews on cardiovascular effects have also been recently published (Biscione, Pignalberi, Totteri, Messina, & Altamura, 2007;Tziomalos, Athyros, & Mikhailidis, 2007;vonSchacky & Harris, 2007;Das, 2008). vonSchacky and Harris (2007) proposed the omega-3 index (percentage of EPA + DHA of total fatty acids in red blood cells) as a risk factor for sudden cardiac death and concluded that this index should be higher than 8%.…”
Section: Omega-3 Fatty Acids and Human Healthmentioning
confidence: 99%
“…The latest overview found about the effect of omega-3 fatty acids in rheumatoid arthritis was published in 1998 (Ariza-Ariza, MestanzaPeralta, & Cardiel, 1998) although there is a more recent one (2006) not published in English (Stancík, Rovenský, & Stančíková, 2006). Several recent reviews on cardiovascular effects have also been recently published (Biscione, Pignalberi, Totteri, Messina, & Altamura, 2007;Tziomalos, Athyros, & Mikhailidis, 2007;vonSchacky & Harris, 2007;Das, 2008). vonSchacky and Harris (2007) proposed the omega-3 index (percentage of EPA + DHA of total fatty acids in red blood cells) as a risk factor for sudden cardiac death and concluded that this index should be higher than 8%.…”
Section: Omega-3 Fatty Acids and Human Healthmentioning
confidence: 99%
“…In addition, frying was a common food preparation method among South Asians [94]. n-3 polyunsaturated fatty acids (PUFA) confer CVD protection through a variety of mechanisms [98]. South Asians show a lower consumption of n-3 PUFA than Europeans [96].…”
Section: Dietmentioning
confidence: 99%
“…La importancia del consumo de productos pesqueros para la salud ha sido ampliamente reportada en la literatura 4 , entre sus beneficios se encuentran la presencia de nutrientes importantes para el bienestar humano, entre ellos los ácidos grasos polinsaturados como el EPA (ácido eicosapentaenoico C20:5) y DHA (ácido docosahexaenoico C22:6) que ayudan en la prevención de enfermedades 5 ; ayudan a mantener un buen funcionamiento del sistema cardiovascular 6,7 ; proporciona protección de las membranas plasmáticas neuronales por lo cual previene enfermedades como el Alzheimer 8 , adicionalmente su consumo se ha asociado con menor prevalencia de diabetes 9 .…”
Section: Introductionunclassified